Critical Remarks on the USE in Mathematics: Quality of the Test and the Examination Procedure - Ivanov, Aleksandr (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The paper discusses in detail the problems of the USE (Unified State Examination) in mathematics. Specifically, the paper studies the examination procedure and determines how well the examination stands up to Well-known technical, methodological, and didactical characteristics of efficient tests. The paper presents results concerning the main parameters of the test: its form, length (number of assignments) and duration. The author suggests procedures to organize the test that would allow the researcher to follow the whole procedure «from inside» by measuring the time needed to perform each separate assignment. This technology has been tested many times, and it has many advantages: it prevents mistakes in the scanning the completed tests, its cost is low, and it can be used to objectively measure the level of competence of students.